2020
DOI: 10.18662/rrem/12.2sup1/302
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Challenges – the Impact of COVID-19 on Agricultural Higher Education in Ukraine

Abstract: Due to the COVID-19 outbreak, higher education institutions all over the world have been faced with the urgent need for going online. Still, higher education institutions in Ukraine have met this new challenge with significant gaps in online education expertise. In this paper, we provide a brief overview of the major challenges that have become relevant to Ukrainian agricultural universities in the pandemic period. In particular, we tried to evaluate the main areas where the major interventions have been carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Aspects of e-learning most affected by the transition during the COVID-19 pandemic were discussed in academic publications recently. For example, Knysh and Dudziak ( 2020 ) highlight the major relevant challenges for Ukrainian agricultural universities in the pandemic period: access to relevant ICT infrastructure, methodological support and academic staff training. Marshall et al ( 2020 ) discussed the issues that higher educational leaders were confronted with: equity, access to technology, teacher training, resources, financing, and the well-being of students and staff.…”
Section: Academic Continuity and Resilient Universitymentioning
confidence: 99%
“…Aspects of e-learning most affected by the transition during the COVID-19 pandemic were discussed in academic publications recently. For example, Knysh and Dudziak ( 2020 ) highlight the major relevant challenges for Ukrainian agricultural universities in the pandemic period: access to relevant ICT infrastructure, methodological support and academic staff training. Marshall et al ( 2020 ) discussed the issues that higher educational leaders were confronted with: equity, access to technology, teacher training, resources, financing, and the well-being of students and staff.…”
Section: Academic Continuity and Resilient Universitymentioning
confidence: 99%
“…For many institutions, the sudden transition to remote teaching constituted a prolonged emergency. Capacity for remote teaching depends on information and communication technology infrastructure; available training, support, and funding; institutional and departmental teaching culture; student preparedness for remote learning; and faculty workload and motivation, among other factors (Knysh & Dudziak, 2020;Meyer & Xu, 2007). In past research, instructors reported that teaching online imposed a substantial workload above teaching in-person, typically requiring weeks or months more preparation (Freeman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic education (which may also be referenced as distance learning, eLearning, pandemic learning, or distance education) is atypical of the regular online learning structures previously found in higher education; instead, it is a form of emergency eLearning (Nordmann et al 2020 ). While some see the innovations developed in online learning as an opportunity to improve education (Knysh and Dudziak 2020 ), others caution that emergency eLearning should not be normalized as a replacement for face-to-face learning (Murphy 2020 ).…”
Section: Current Literaturementioning
confidence: 99%